(untitled) (ENTHYMEMA, 2018)
Si recensisce Lawtoo, Nidesh. Il fantasma dell’io: la massa e l’inconscio mimetico. Mimesis, 2018. This is the review of the Italian edition of Lawtoo, Nidesh. Il fantasma dell’io: la massa e l’inconscio mimetico. Mimesis, 2018.